Challenges and Coping Strategies of Female Detectives in Bahir Dar City Administration, Amhara Region, Ethiopia - Demissie, Sewmehon; Tassew, Tigist (Ethiopian Journal of Social Sciences, 2021)
Crime investigation is an applied science which includes the study of evidence, used to recognize, detect, and verify the guilt of illicit activities. Males are the main actors of crime investigation in Ethiopia though few female police officers are involved in this job. Therefore, the objective of this study was to identify the challenges that female detectives face during their careers and the coping mechanisms they used to overcome problems in the study site through exploring their lived experiences. To achieve these objectives, a qualitative approach with phenomenological research design was employed. Primary data were collected from eight purposively selected participants using in-depth interviews and were analyzed thematically. The findings of the research indicated that the motivation for women to join the police force were found to be peer pressure, influence of family members, interest of helping others and marital relationship. Even though female officers enjoyed opportunities like psychological satisfaction, being role models for family members, and enhancing social acceptance; the findings of this study indicated that female detectives face tremendous and serious challenges throughout their careers. Some of these challenges include administrative problems, low scale salary, lack of conducive work environment, family responsibility, attitudinal challenges, discrimination, and harassment. To overcome these challenges, female officers use the following coping mechanisms. These include confronting the administration, appealing to concerned bodies, and finding family support. In conclusion, the working condition for female detectives in the study area was dominated by challenging work environment that was both extensive and multifaceted in nature. Therefore, all concerned bodies should properly address the existing complex problems of female detectives through empowering their capacity and participation.